2023
DOI: 10.1111/cas.15788
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between driver genes shape the signaling pathway landscape and direct hepatocellular carcinoma therapy

Abstract: Hepatocellular carcinoma (HCC) is one of the most lethal malignancies, whose initiation and development are driven by alterations in driver genes. In this study, we identified four driver genes (TP53, PTEN, CTNNB1, and KRAS) that show a high frequency of somatic mutations or copy number variations (CNVs) in patients with HCC. Four different spontaneous HCC mouse models were constructed to screen for changes in various kinase signaling pathways. The sgTrp53 + sgPten tumor upregulated mTOR and noncanonical nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Importantly, the treatment resulted in the downregulation of pSTAT3 and stemness markers such as Nanog, CD133, Klf4, Oct4, and Sox2 [134]. In another study, tumors induced by activated beta-catenin and mTOR signaling were highly susceptible to napabucasin, which strongly inhibited the proliferation of the tumor cells [135].…”
Section: In Vitro Studies Targeting the Jak/stat Signaling Pathway In...mentioning
confidence: 96%
See 1 more Smart Citation
“…Importantly, the treatment resulted in the downregulation of pSTAT3 and stemness markers such as Nanog, CD133, Klf4, Oct4, and Sox2 [134]. In another study, tumors induced by activated beta-catenin and mTOR signaling were highly susceptible to napabucasin, which strongly inhibited the proliferation of the tumor cells [135].…”
Section: In Vitro Studies Targeting the Jak/stat Signaling Pathway In...mentioning
confidence: 96%
“…In vitro and in vivo animal studies have demonstrated that napabucasin has a strong anti-tumor effect on HCC, as the STAT3 inhibitor suppresses cell viability and proliferation, as well as downregulates expression of stemness genes [134,135]. Based on promising preclinical results, a clinical trial evaluated the co-administration of sorafenib and napabucasin for potential benefits in advanced HCC patients over sorafenib treatment alone.…”
Section: Clinical Studies Targeting the Jak/stat Signaling Pathway In...mentioning
confidence: 99%
“…Importantly, the treatment resulted in the downregulation of pSTAT3 and stemness markers such as Nanog, CD133, Klf4, Oct4, and Sox2 [ 158 ]. In another study, tumors induced by activated beta-catenin and mTOR signaling were highly susceptible to napabucasin, which strongly inhibited the proliferation of the tumor cells [ 159 ].…”
Section: In Vitro and In Vivo Studies Targeting The Jak/stat Signalin...mentioning
confidence: 99%
“…In vitro and in vivo animal studies have demonstrated that napabucasin has a strong antitumor effect on HCC, as the STAT3 inhibitor suppresses cell viability and proliferation, as well as downregulating expression of stemness genes [ 158 , 159 ]. Based on promising preclinical results, a clinical trial evaluated the co-administration of sorafenib and napabucasin for potential benefits in advanced HCC patients over sorafenib treatment alone.…”
Section: Clinical Studies Targeting the Jak/stat Signaling Pathway In...mentioning
confidence: 99%